2010
DOI: 10.1158/1541-7786.mcr-10-0362
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Bidirectional Regulation of the MutS Homolog 2 by Transforming Growth Factor β Contributes to Chemoresistance in Breast Cancer Cells

Abstract: The TGF-b, a tumor suppressive cytokine in normal cells, is abused in cancer to promote the malignancy. In this study, we reported that TGF-b downregulated the mutS homolog 2 (MSH2), a central component of the DNA mismatch repair (MMR) system, in HER2-transformed MCF10A mammary epithelial cells and in breast cancer (BC) cells. This was mediated by a TGF-b-induced micro RNA (miRNA), miR-21, which targeted the 3 0 untranslated region of MSH2 mRNA and downregulated its expression. A negative correlation between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 35 publications
3
72
0
Order By: Relevance
“…Previous studies have demonstrated that TGF-β1 decreased the sensitivity of cancer cells to chemotherapeutic drugs (8,9). In addition, miR-21 may modulate the chemosensitivity of breast cancer cells to DOX (21).…”
Section: Downregulation Of Mir-21 Decreases Resistance Of Breast Cancmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have demonstrated that TGF-β1 decreased the sensitivity of cancer cells to chemotherapeutic drugs (8,9). In addition, miR-21 may modulate the chemosensitivity of breast cancer cells to DOX (21).…”
Section: Downregulation Of Mir-21 Decreases Resistance Of Breast Cancmentioning
confidence: 98%
“…Previous studies have demonstrated that TGF-β1 facilitates breast carcinoma metastasis by promoting epithelial-mesenchymal transition (EMT) in tumor cells (6,7). Additionally, TGF-β1 was previously associated with chemoresistance, and increased TGF-β1 levels led to poor clinical outcomes in a number of types of cancer, including breast cancer (8,9). Multiple pathways are involved in TGF-β1 signaling (10); however, the downstream molecular pathways for TGF-β1-mediated breast cancer metastasis and chemoresistance remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA extraction, reverse transcription (RT), and real-time quantitative PCR (qPCR) were performed as described previously (49). Primer sequences used were as follows: 5=-CC TGTTTCCTTGAGATCAGCTGC-3= and 5=-GTGAGGGAAGAAAGTT GGGAGCG-3= for the Chr7-6 T␤RI-binding site, 5=-CCCATAACCCCT GAGGGTAG-3= and 5=-CTCAGGCGGCAGTCATAGA-3= for the Chr7-193 T␤RI-binding site, 5=-GAGCCGCGAGAAGTGCTAGCTCG-3= and 5=-CTGGAGCACTGTCTGCGCACACC-3= for the Chr6-6 T␤RI-binding site, 5=-GGAAGTGTTGAAGGGAGGTGGCA-3= and 5=-CAAACCG TGCCTGGAAGTCAACG-3= for the Chr11-110 T␤RI-binding site, 5=-C ACTGCAGCACTTGAAGGAGG-3= and 5=-TGAGGCAGAGGCTGCCA TCTA-3= for the Chr15-7 T␤RI-binding site, 5=-TGGAGCCTCTTACAC CCAGT-3= and 5=-GCTTTCGGAGATGTTGCTTC-3= for human epidermal growth factor receptor (EGFR) isoform a, 5=-AACAACACCC TGGTCTGGAA-3= and 5=-TGAAGCAAAGGGAGAAATTGA-3= for human EGFR isoform b, 5=-GGATATTCTGAAAACCGTAAAGGAAA-3= and 5=-CGAAAAGTTCTCTCTAAAACACTGATT-3= for human EGFR isoform c, 5=-CCAGTGTGCCCACTACATTG-3= and 5=-CGCTGCCAT CATTACTTTGA-3= for human EGFR isoform d, 5=-GGCTCTGGAGGA AAAGAAAG-3= and 5=-CAATGAGGACATAACCAGCCAC-3= for all EGFR isoforms, 5=-GGCTCTGGAGGAAAAGAAAG-3= and 5=-AGAAC GAAACGTCCCGTTCCTC-3= for primary EGFR transcripts, and 5=-AC CACAGTCCATGCCATCAC-3= and 5=-TCCACCACCCTGTTGCTGT A-3= for human glyceraldehyde-3-phosphate dehydrogenase (GAPDH) (as a control).…”
Section: Methodsmentioning
confidence: 99%
“…The tumor suppressor p53 has a central role in the activation of genes in multiple pathways, including cellcycle regulation, tumor suppression, and apoptosis. miR-125b and miR-504 have been identified as negative regulators of p53 in several types of human cells [91,92] . Interestingly, miR-605, and miR-143/miR-145 are post-transcriptionally activated by p53 and, subsequently, target Mdm2, leading to rapid accumulation of p53 [93,94] .…”
Section: Pan D Et Al Epigenetic Modulation and Ionizing Radiationmentioning
confidence: 99%